Digital Marketing-Based Entrepreneurial Resilience dalam Memediasi Strategi Pemasaran Kewirausahaan terhadap Kinerja Pemasaran UMKM di Barlingmascakeb - Setyawan, Antonius Ary; Racma, Dhany Faizal (https://jurnal.binamandiri.ac.id/, 2024)
MSMEs in Indonesia face various challenges, including limited digitalization capabilities, lack of product innovation, marketing, and difficulty adapting to environmental changes, and slow response to dynamic market competition, all of which hinder the improvement of their marketing performance. The purpose of this study is to provide an accurate analysis of the role of digital marketing-based entrepreneurial resilience in mediating entrepreneurial marketing strategies on the marketing performance of MSMEs in Banjarnegara, Purbalingga, Banyumas, Cilacap, Kebumen (Barlingmascakeb), which is a new concept in helping to overcome MSME marketing performance. This study is categorized as explanatory research, namely research that aims to explain the causal relationship between variables through hypothesis testing. The approach to this study is a survey approach. The population in this study were all batik MSMEs in Banjarnegara, Purbalingga, Banyumas, Cilacap, Kebumen (Barlingmascakeb) totaling 259. Of the total population of 259, only 107 use digital marketing so this study uses a sampling technique with purposive sampling of 107 respondents in this study. The results of this study are that entrepreneurial marketing does not have a positive effect on marketing performance, entrepreneurial marketing has a positive effect on digital marketing-based entrepreneurial resilience, digital marketing-based entrepreneurial resilience has a positive effect on marketing performance and digital marketing-based entrepreneurial resilience mediates the relationship between entrepreneurial marketing and marketing performance.